2004
DOI: 10.3201/eid1007.030411
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis ofPlasmodium ovaleVariants

Abstract: Sequence analyses of six isolates from Southeast Asia supports dividing species into types

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 29 publications
6
66
1
Order By: Relevance
“…32,41 On the basis of analysis of sequences from three different P. ovale genes, a recent report segregates P. ovale into two clades, classic and variant, that are as divergent as separate species. 31 Analysis of partial 18S rRNA gene sequences from the two P. ovale isolates described here indicates they are both members of the classic clade (data not shown). It would be interesting to obtain the MSP1 sequence for a member of the P. ovale variant clade, and compare it to the sequences presented here to see if it supports the contention that the two clades represent separate species.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…32,41 On the basis of analysis of sequences from three different P. ovale genes, a recent report segregates P. ovale into two clades, classic and variant, that are as divergent as separate species. 31 Analysis of partial 18S rRNA gene sequences from the two P. ovale isolates described here indicates they are both members of the classic clade (data not shown). It would be interesting to obtain the MSP1 sequence for a member of the P. ovale variant clade, and compare it to the sequences presented here to see if it supports the contention that the two clades represent separate species.…”
Section: Discussionmentioning
confidence: 81%
“…31 BLAST analysis showed 100% homology of the amplicon sequences with "classic-type" P. ovale 18S rRNA gene sequences in GenBank (data not shown). For specimens identified as co-infected with P. falciparum and P. malariae , the 18S rRNA gene sequence chromatograms suggested the presence of multiple sequences.…”
Section: Identification Of Parasitemic Donors Whole Blood Frommentioning
confidence: 99%
“…Sensitive molecular techniques that allow the sensitive detection and the accurate identification of Plasmodium parasites, on the basis of amplification of their small-subunit rRNA (ssrRNA) gene, revealed that the prevalences of P. malariae and P. ovale infections were higher than previously thought (9,14,18,21,25). Sequence variations were, however, detected in these genes in P. malariae and, in particular, in P. ovale, in which two types were found (4,8,28,30). This led to the design of novel oligonucleotide primer combinations to increase the accuracy of P. ovale detection (5,10,19).…”
mentioning
confidence: 99%
“…The efficacy and the accuracy of detection rely on a lack of variation in the target sequences to which the amplification primers hybridize. To date, evidence of polymorphisms in the ssrRNA genes was obtained for P. ovale and P. malariae (4,8,28,30), mainly isolates collected in Southeast Asia, but not for P. falciparum and P. vivax. This might reflect a different and possibly more ancient evolutionary pathway for P. malariae and P. ovale.…”
mentioning
confidence: 99%
“…Kodak BioMax MS Films were obtained from Perkin Elmer (France). In addition, intensifying screens (Kodak BioMax TranScreen LE, Perkin Elmer) were used for TLC of [1][2][3] H]ethanolamine-labeled metabolites. Radioactive spots were scraped off directly into scintillation vials and radioactivity was determined by liquid scintillation counting (Ultimagold, Perkin Elmer) and counted in a Beckman LS 6500 spectrometer.…”
Section: Syntenic Regions Corresponding To the Genomic Context Of Phomentioning
confidence: 99%